Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How can I show that $\lfloor (2+\sqrt{3})^n \rfloor $ is odd and that $2^{n+1}$ divides $\lfloor (1+\sqrt{3})^{2n} \rfloor+1 $ ?

$$ u_{n}=(2+\sqrt{3})^n+(2-\sqrt{3})^n=\sum_{k=0}^n{n \choose k}2^{n-k}(3^{k/2}+(-1)^k3^{k/2})\in\mathbb{2N} $$

$$ 0\leq (2-\sqrt{3})^n \leq1$$

$$ (2+\sqrt{3})^n\leq u_{n}\leq 1+(2+\sqrt{3})^n $$

$$ (2+\sqrt{3})^n-1\leq u_{n}-1\leq (2+\sqrt{3})^n $$

$$ \lfloor (2+\sqrt{3})^n \rfloor=u_{n}-1\in\mathbb{2N}+1 $$

share|improve this question
    
Related to math.stackexchange.com/questions/48508/… –  lhf Dec 23 '11 at 11:30

2 Answers 2

Hint for the first part: Consider $u_n = (2+\sqrt{3})^{n} + (2-\sqrt{3})^{n}$. Prove that $u_n$ is always an even integer and that $u_n = \lceil (2+\sqrt{3})^n \rceil$. Use that $(2-\sqrt{3})^{n}\to 0$.

(This has now been incorporated into the edited question.)

Hint for the second part: Consider $v_n = (1+\sqrt{3})^{n} + (1-\sqrt{3})^{n}$. Find a second-order recursion for $v_n$ based on the quadratic equation that defines $1\pm\sqrt{3}$.

share|improve this answer
    
You don't really need $(2-\sqrt 3)^n\to 0$, just that $0<(2-\sqrt 3)^n<1$, right? And you've confused $u_n$ and $u_2n$ in the second part. –  Thomas Andrews Dec 22 '11 at 15:18
    
@Thomas, right, just that $0<(2-\sqrt 3)^n<1$. I've fixed the typo, thanks. –  lhf Dec 22 '11 at 15:23
    
Could someone detail the second part? –  Chon Dec 22 '11 at 17:20
    
@PlaneChon-Ju, actually, I don't think that the second part is true. The numbers in the sequence are 2,4,14,52,194,724,2702,10084,37634,140452,524174,1956244,7300802,27246964 and they are either 2 or 4 times an odd number. –  lhf Dec 22 '11 at 18:40
    
Sorry, the quantity is actually $\lfloor (1+\sqrt{3})^{2n} \rfloor+1 $ –  Chon Dec 22 '11 at 21:19

You can use recurrences such as $$f(n)=4f(n-1)-f(n-2)+2$$ or $$f(n)=5f(n-1)-5f(n-2)+f(n-3)$$ starting at $f(0)=1, f(1)=3$.

Then show the various results by induction.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.